Alumina supported/unsupported mixed oxides of Ca and Mg as heterogeneous catalysts for transesterification of Nannochloropsis sp. microalga's oil - Teo, Siow Hwa; Yap, Taufiq Yun Hin; Ng, F. L. (Elsevier, 2014)
In this study, calcium magnesium (CaMgO) and alumina (Al2O3) supported CaMgO mixed oxide catalysts were prepared via pH-controlled co-precipitation (Na2CO3 and NaOH as a precipitant) for transesterification of crude Nannochloropsis oculata (N. oculata) oil with methanol. The catalysts were characterized by means of Thermogravimetric analyses (TGA), X-ray diffraction (XRD), Fourier transform-infrared (FTIR), Temperature programmed desorption of CO2 (CO2-TPD), Inductively coupled plasma–atomic emission spectrometer (ICP–AES) and Scanning electron microscopy (SEM) analysis. At optimization condition, CaMgO mixed oxide catalyst showed 75.2% of fatty acid methyl ester (FAME) yield with catalyst loading of 20 wt.% at 3 h. Meanwhile, the supported CaMgO mixed oxide catalyst gave a higher FAME yield of 85.3% with catalyst loading of 10 wt.% at same conditions. Besides, the reusability study of catalyst was performed to investigate the stability and durability of supported/unsupported catalysts. The high content of Ca2+ and Mg2+ precipitated on Al2O3 supported CaMgO mixed oxide catalyst tend to increase the total basicity and provide more active sites for transesterification reaction. Moreover, better moisture resistant on the Al2O3 supported CaMgO mixed oxide catalyst compared with CaMgO mixed oxide catalyst, which is favourable for transesterification reaction on high water content microalgae oil.